An investigation of the challenges constraining the performances of Nigeria institute of international relation - Modu Lawan Gana; Hadiza Mali Bukar; Maryam Mala (Journal of Management and Science, 2023)
The research focus on the examination of the roles of Nigeria Institute of International Relation in promoting Nigeria diplomatic relation. The study is approach on qualitative approach designed on phenomenological research. The empirical data was collected through in-depth interviews involving face to face method. Ten (10) respondents were engaged in the study. The primary source which contain an open-ended question administered to the respondents was triangulated with data from secondary source such as journals, articles, textbooks. and media. The research finds out that Nigeria Institute of International affairs have a positive role on the policy formulation processes of Nigeria. However, it revealed that the institution was bedeviled with several challenges such as financial, Administrative, infrastructural and political. While it concludes that the role of the Institute is inevitable for the promotion of Nigeria foreign policy interest, it recommends that the Institute should strive to expand its in-house revenue to manage its affaire. It also recommends the need for strong legislation that stipulate the areas of jurisdiction between and among the Institute and other related agencies and the ministry.